Improved algorithm for evaluation of lightning induced overvoltage on distribution lines - Izadi, Mahdi (2010)
Lighting is a natural phenomenon and can affect the performance of the power lines in two different ways, i.e. direct and indirect strikes. In case of direct strike, it occurs when the tower or shield wire is struck by the lightning and creates an induced overvoltage on phase conductors or shielding wire. Whilst for indirect strikes, it could happen if a lightning strike near the power lines and it produces electric and magnetic fields which depend on a number of factors such as lightning return stroke current and lightning parameters, the distance from power lines and conductivity of the ground. Induced overvoltage is a major cause of interruption on distribution networks and specific research is needed in evaluating the amount of overvoltage induced on such network accurately without many assumptions involved.